Technology at your service [ - Sears, Twila (Meridian Education Corporation, 2004)
This program explores how the equipment we often take for granted has become an integral part of our daily lives. At work, at school, and in the home, technology has become one of our most valuable resources. Robots, computers, and many other types of high-tech hardware are introduced